Semiquantitative immunohistochemical marker staining and localization in canine thyroid carcinoma and normal thyroid gland. (1st August 2014) - Pessina, P.; Castillo, V.; Sartore, I.; Borrego, J.; Meikle, A.
Abstract: Immunoreactive proteins in follicular cells, fibroblasts and endothelial cells were assessed in canine thyroid carcinomas and healthy thyroid glands. No differences were detected in thyrotropin receptor and thyroglobulin staining between cancer and normal tissues, but expression was higher in follicular cells than in fibroblasts. Fibroblast growth factor‐2 staining was more intense in healthy follicular cells than in those of carcinomas. Follicular cells in carcinomas presented two‐ to three‐fold greater staining intensity of thyroid transcription factor‐1 and proliferating cell nuclear antigen, respectively, than healthy cells, and a similar trend was found for the latter antigen in fibroblasts. Vascular endothelial growth factor staining was more intense in the endothelial cells of tumours than in those of normal tissues. In conclusion, greater expression of factors related to proliferation and angiogenesis was demonstrated in several cell types within thyroid carcinomas compared to healthy tissues, which may represent mechanisms of tumour progression in this disease.